Kejadian Human Immunodeficiency Virus (HIV) di Kota Palembang - Rosnita, Rosnita; Murni, Nani Sari; Wahyudi, Arie (Universitas Baiturrahim, 2024)
Human Immunodeficiency Virus (HIV) cases in South Sumatra are among the top 10 in Indonesia and Palembang City has the highest case. This study aims to analyse the frequency distribution of gender, address, marital status, history of blood transfusion, history of sexually transmitted diseases, number of sexual partners, drug use status, alcohol drinking habits, type of work, HIV history in partners, condom use status and socioeconomic, risky sexual behaviour and HIV incidence in Palembang City. This type of research is descriptive. The sample technique used was total sampling. Data collection was done by questionnaire, analysed using Univariate analysis. The results obtained frequency distribution of gender: 83.0% male, 89.4% lived in Palembang city, 69.1% unmarried, 76.6% had a history of receiving blood transfusions, 53.2% had a history of sexually transmitted diseases, 61. 7% had more than 1 sexual partner, 80.9% had a history of drug use, 52.1% did not have a habit of drinking alcohol, 72.3% had a risky job, 76.6% had a partner who had HIV, 77.7% always used condoms, 77.7% had an income below minimum wage, 68.1% did not have a history of risky sexual behaviour. Conclusion: HIV patients in Palembang City in 2024 are mostly men who live in Palembang City, unmarried, have a history of blood transfusions and other sexually transmitted diseases, have more than 1 sexual partner, have ever consumed drugs, have jobs that are at risk of HIV transmission, have sexual partners with HIV sufferers, use condoms during intercourse, earn below the minimum wage.